Synthesis of Diarylmethanes through Palladium-Catalyzed Coupling of Benzylic Phosphates with Arylsilanes - Zhang, Pengbo; Xu, Jian; Gao, Yuzhen; Li, Xueqin; Tang, Guo; Zhao, Yufen (Synlett, 2014)
An efficient approach to the benzylation of arenes has been developed. The reactions described provide straightforward access to diarylmethanes through Pd-catalyzed coupling of benzylic phosphates with arylsilanes in good to excellent yields. The reaction tolerates a wide range of functionalities such as halide, alkoxyl, and nitro groups.
Keywords: palladium; diarylmethane; arene; benzylation; Hiyama cross-coupling